Evidence on Job Search Models from a Survey of Unemployed Workers in Germany - Stefano Della Vigna; Jörg Heining; Johannes F. Schmieder; Simon Trenkle (Institute of Labor Economics (IZA), 2020)
The job finding rate of Unemployment Insurance (UI) recipients declines in the initial months of unemployment and then exhibits a spike at the benefit exhaustion point. A range of theoretical explanations have been proposed, but those are hard to disentangle using data on job finding alone. To better understand the underlying mechanisms, we conducted a large text-message-based survey of unemployed workers in Germany. We surveyed 6,800 UI recipients twice a week for 4 months about their job search effort. The panel structure allows us to observe how search effort evolves within individual over the unemployment spell. We provide three key facts: 1) search effort is flat early on in the UI spell, 2) search effort exhibits an increase up to UI exhaustion and a decrease thereafter, 3) UI recipients do not appear to time job start dates to coincide with the UI exhaustion point. A model of reference-dependent job search can explain these facts well, while a standard search model with unobserved heterogeneity struggles to explain the second fact. The third fact also leaves little room for a model of storable offers to explain the spike.
Keywords: J64; J65; D91; 330; unemployment; job search; reference dependence; survey